Impact of blastocyst grading and blastocyst biopsy dates on the clinical outcomes of patients undergoing preimplantation genetic testing - Tan, Chang; Wang, Xiliang; Zou, Pengshu; Wei, Wei; Yan, Li; Wang, Kaiyue; Yu, Yuexin (Frontiers in Endocrinology, 2024)
Background: Preimplantation genetic testing (PGT) allows for the evaluation of embryo genetic information prior to implantation, enabling the selection of normal embryos for transfer and ultimately leading to better pregnancy outcomes. In this study, we explored factors that influence clinical outcomes of patients undergoing PGT. The effects of blastocyst grading and biopsy dates on clinical outcomes were also analyzed. Methods: The clinical data and pregnancy outcomes of 428 PGT cycles performed in the Reproductive Medicine Department of the Northern Theater General Hospital between January 2017 and December 2022 were retrospectively analyzed. Multifactorial logistic regression analysis and nomograms were used to determine factors influencing pregnancy outcomes. The impact of D5 blastocysts (290 cycles) and D6 blastocysts (138 cycles) with different quality levels on clinical outcomes was also compared. Results: Multifactorial logistic regression analysis showed that age, BMI, endometrial thickness, and embryo quality of women affected PGT clinical outcomes. Women aged <40 years or with a body mass index (BMI) >18.5 and endometrial thickness>1.0 cm had a significantly higher pregnancy success rate. Compared to that of D6 blastocyst biopsy, D5 blastocyst biopsy was associated with a higher pregnancy success rate but a similar live birth rate. No significant differences were observed in the pregnancy and live birth rates of D5 and D6 high-quality blastocysts.To achieve better pregnancy outcomes after PGT, considering blastocyst grading and biopsy dates when transferring embryos is essential for improving pregnancy outcomes. Furthermore, patients should adjust their BMI, endometrial receptivity, and endometrial thickness and pattern.